Lachlan McIntosh Papers in the University of Georgia Libraries - Jackson, Harvey H. (Georgia Open History Library, 1968)
Lachlan McIntosh Papers documents Georgia's history during the early Revolutionary War period through the experiences of General Lachlan McIntosh, a prominent Scottish American political and military leader. These papers provide a behind-the-scenes glimpse into political decisions and military movements throughout the first two years of the war. This collection illuminates McIntosh's instrumental role in the events of the early Revolutionary War period through his correspondence, from reports to new commander in chief George Washington to various letters with other military and political leaders of the time. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.